PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEBSITE PADA NTI FASHION MENGGUNAKAN METODE RAD - Anggitha Lidya Anggraini (2023)
The rapid development of technology makes many people try to take advantage of technology properly. This research was conducted to design a website-based sales information system for UMKM called NTI Fashion. At NTI Fashion, all sales data management is still done manually and there are no online orders and dissemination of information related to NTI Fashion on social media. So this research was conducted with the aim of designing a website-based sales information system at NTI Fashion by analyzing existing problems using PIECES analysis. The method used in developing this system is by using the Rapid Application Development (RAD) method. The purpose of using this method is because the development of this system involves users in designing information systems to suit their needs. Because this research focuses on user needs, the RAD method is suitable if there is a case where the user wants to add or remove a feature when testing using a prototype. The results of this study are in the form of a website-based sales information system where later customers can view information related to NTI Fashion and can place orders online and owners can manage data and information quickly to make it more effective and efficient.